Young Woman’s Learning of Taste in Fashion Style Through Their Engagements With TikTok Influencer - Eririan Kloer, Latissya; Surayya Ulfa, Nurist; Yusriana, Amida (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Over the last ten years, fashion shopping in Indonesia has become more popular and important for the country's economy. Especially among young women, social media like TikTok is a big part of how they learn about and choose their clothes. People follow influencers on TikTok who shows them what's cool and helps them decide what to wear. This study wants to understand how these influencers on TikTok affect what young women like and buy when it comes to fashion. By employing the Taste Regime Theory by Zeynep Arsel and Jonathan Bean and integrating the concept of consumer identity projects. This research utilizes the a qualitative research method that uses the Interpretative Phenomenological Analysis (IPA) method. In this study, the researcher conducted in-depth interviews with three young woman aged 17-25 who are active users of the TikTok application. This study seeks to uncover how people develop their fashion taste through TikTok influencers and the resulting impact on their personal style preferences. The findings also show that fashion choices are not solely based on trends but also reflect personal beliefs and societal perceptions. The study contributes to Zeynep Arsel and Jonathan Bean concept by emphasizing the impact of digital platforms and influencers on personal expression and societal norms. The research reveals fashion taste among young women and how fashion serves as a medium for personal expression and meaningful decision-making. Overall, the study suggests that developing fashion taste is a complex process influenced by personal expression, societal influence, social media impact and guidance form influential figures.